2007
DOI: 10.2460/javma.230.9.1356
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and respiratory effects of butorphanol and morphine in turtles

Abstract: Although widely used in reptile species, butorphanol may not provide adequate antinociception for invasive procedures and caused short-term respiratory depression in red-eared slider turtles. In contrast, morphine apparently provided antinociception but caused long-lasting respiratory depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
11

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 20 publications
2
78
1
11
Order By: Relevance
“…Subsequent investigations have indicated that higher doses of naloxone (0.2 mg/kg) are required to consistently and fully reverse the effects of morphine in turtles (Sladky et al, 2007). This regime has been successfully used for a variety of chelonian species and appears to have significant benefits for field use.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have indicated that higher doses of naloxone (0.2 mg/kg) are required to consistently and fully reverse the effects of morphine in turtles (Sladky et al, 2007). This regime has been successfully used for a variety of chelonian species and appears to have significant benefits for field use.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, j-opioid receptor agonists such as butorphanol and nalbuphine are more effective analgesics in avian species than are l agonists [32]. The efficacy of different classes of opioids in reptile species has also been extensively studied, and analgesia in these species appears to be mediated through the l-opioid receptor, much like mammals [33].…”
Section: Opioidsmentioning
confidence: 99%
“…When a fluid deficit is clearly identified or the hydration status of the patient is unknown, peri-anesthetic fluid therapy is indicated to replace the deficit in active circulating volume and restore tissue perfusion and nol, even at dosages largely exceeding the mammalian therapeutic doses, did not have any effect on thermal threshold (Sladky et al 2007). The analgesic action of morphine (1.5 mg/kg) in chelonians appears to have a time of onset of 2-8 hours postadministration and duration of more than 24 hours.…”
Section: Fluid Therapymentioning
confidence: 99%
“…The analgesic action of morphine (1.5 mg/kg) in chelonians appears to have a time of onset of 2-8 hours postadministration and duration of more than 24 hours. Unfortunately this analgesic effect is coupled with a significant, longlasting respiratory depression (Sladky et al 2007). Meperidine, a synthetic μ pure agonist, induced significant decrease in the duration of limb retraction after formalin injection in Speke's hinged tortoise (Kinixy's spekii) at the dose of 20 mg/kg.…”
Section: Fluid Therapymentioning
confidence: 99%